AN ELECTRICAL ENGINEERING ANALYSIS OF ENERGY-EFFICIENT LIGHTING AND CLIMATE CONTROL SYSTEMS FOR MODERN MOSQUES - Luis Santos; Sulaiman Sulaiman; Thi Lan (Journal of Moeslim Research Technik, 2025)
The increasing demand for energy-efficient solutions in public buildings has led to a growing interest in sustainable technologies for modern mosques. As places of worship with high foot traffic and long operating hours, mosques represent an ideal setting for implementing energy-efficient lighting and climate control systems. However, there is limited research on optimizing energy usage in these religious spaces while maintaining comfort and functionality. This study aims to analyze the energy efficiency of lighting and climate control systems in modern mosques and propose improvements that align with sustainable energy practices. Using an electrical engineering approach, this research employs simulation models and energy consumption data to evaluate current systems in selected mosques. Various energy-efficient technologies, including LED lighting, smart thermostats, and automated climate control systems, are assessed for their potential in reducing energy consumption. The results indicate that integrating energy-efficient lighting and climate control solutions can significantly reduce energy use, with potential savings of up to 40%. The study concludes that adopting these systems not only promotes sustainability but also aligns with the Islamic principles of conservation and stewardship of resources. Recommendations for mosque administrators include investing in smart energy solutions and regular monitoring to optimize energy consumption.